Preparation and investigation of mefenamic acid – polyethylene glycol – sucrose ester solid dispersions - Fülöp Ibolya; Gyéresi Árpád; Kiss Lóránd; Deli Mária A.; Croitoru Mircea Dumitru; Szabó-Révész Piroska; Aigner Zoltán (Acta Pharmaceutica)
Mefenamic acid (MA) is a widely used non-steroidal antiinflammatory (NSAID) drug. The adverse effects typical of NSAIDs are also present in the case of MA, partly due to its low water solubility. The aim of this study was to increase the water solubility of MA in order to influence its absorption and bioavailability. Solid dispersions of MA were prepared by the melting method using polyethylene glycol 6000 and different types (laurate, D-1216; palmitate, P-1670; stearate, S-1670) and amounts of sucrose esters as carriers. The X-ray diffraction results show that MA crystals were not present in the products. Dissolution tests carried out in artificial intestinal juice showed that the product containing 10 % D-1216 increased water solubility about 3 times. The apparent permeability coefficient of MA across human Caco-2 intestinal epithelial cell layers was high and, despite the difference in solubility, there was no further increase in drug penetration in the presence of the applied additives.